Relation of fibroblast growth factor receptor 2 expression to hepatocellular carcinoma recurrence after liver resection. - Baek Gyu Jun; Woong Cheul Lee; Jae Young Jang; Soung Won Jeong; Young Chang; Sae Hwan Lee; Young Don Kim; Sang Gyune Kim; Gab Jin Cheon; Young Seok Kim; Hong Soo Kim; So Young Jin (PLoS ONE)
Background Hepatocellular carcinoma (HCC) recurrence after liver resection depends upon the stage and histological grade of the tumor and the expression of certain biomarkers. However, it remains unclear which of these factors has the highest predictive value regarding HCC recurrence after surgical resection. Methods This study investigated the associations among clinicopathological characteristics, expression of biomarkers, and HCC recurrence after liver resection. Fifty-four patients having undergone liver resection for HCC were enrolled prospectively, and their data were analyzed retrospectively. Evaluated variables were clinical data, laboratory findings, modified Union for International Cancer Control (UICC) stage, vascular invasion, histological differentiation, and immunohistochemical staining for fibroblast growth factor receptor 2 (FGFR2), vascular endothelial growth factor, and tumor-necrosis-factor-related apoptosis-inducing ligand receptors 1 and 2. Results Mean patient age was 58.6 years (range, 30-71), and the mean and SD for follow-up duration were 51.2 ± 34.8 months. Cumulative 1-, 3-, and 5-year recurrence rates were 32.9%, 53.6%, and 68.1%, respectively. In univariate analysis, FGFR2 (p = 0.026) and Edmonson-Steiner grade (E-S grade) (p = 0.030) were associated with recurrence after resection in HCC patients. In multivariate analyses, increased FGFR2 expression (p = 0.017) was the only significant predictor of HCC recurrence. Conclusions High FGFR2 expression had marginal association with poor E-S grade (p = 0.056). More intensive surveillance of HCC recurrence is warranted in HCC patients with increased FGFR2 expression.